1995
DOI: 10.1017/s0001566000001781
|View full text |Cite
|
Sign up to set email alerts
|

Accommodating a Twin Pregnancy: Maternal Processes

Abstract: The object of this study was to develop a theory of the relationship between a mother and her unborn twins using a qualitative grounded theory methodology. Ten women participated in interviews during the last trimester of a twin pregnancy and again during the early postpartum period. Data provided by these women was analysed using the constant comparative method. Two additional informants were sampled in order to formulate and verify the tentative theory. For women in this study, the findings indicate that mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…The diagnosis of a multiple pregnancy often produces reactions of panic and shock in the future parents (Robin et al, 1992). As the pregnancy progresses, however, women move towards accepting the idea of being pregnant with twins (van der Zalm, 1995). Mothers pregnant with twins more often are hospitalised or confined to bed.…”
mentioning
confidence: 99%
“…The diagnosis of a multiple pregnancy often produces reactions of panic and shock in the future parents (Robin et al, 1992). As the pregnancy progresses, however, women move towards accepting the idea of being pregnant with twins (van der Zalm, 1995). Mothers pregnant with twins more often are hospitalised or confined to bed.…”
mentioning
confidence: 99%
“…Once we had established an initial rapport, my participants were extremely forthcoming. As others researching this population have found (Frank, 1997;Van der Zalm, 1995), my status as someone who had ''been through it'' helped in providing a comfortable and trusting environment for respondents to disclose their feelings and experiences. Oakley (1981) suggested that reciprocal exchange may be more effective than the traditional research interview model (with the informant as ''giver'' and the researcher as ''receiver'') when interviewing women about such issues as pregnancy and childbirth.…”
Section: Building Trust With Women and Their Familiesmentioning
confidence: 87%
“…Based on other studies of this population (e.g., Van der Zalm, 1995), it was expected that participants could be recruited by contacting health care providers and a local twin parenting organization, placing newspaper ads, distributing publicity flyers, and acquiring referrals through snowball sampling. As a former member of the twin parenting organization, I had volunteered on committees whose membership included maternity and infant health care providers.…”
Section: Researcher As Insider: Gaining Access To Pregnant Womenmentioning
confidence: 99%
“…[38] exhorts health professionals practising in hospital and community settings to become aware of the unique needs of multiple-birth women. Refs.…”
Section: Introductionmentioning
confidence: 99%